Star trek, volume 1 godshock ebook - Kelly, Collin (Star Trek (2022), 2023)
Deep Space Nine captain Benjamin Sisko returns in a new ongoing series featuring fan-favorite characters from across the Star Trek universe, sure to thrill new readers and longtime Trekkies alike! Stardate 2378: A bold new era of Star Trek begins! Three years ago, Benjamin Sisko made a courageous sacrifice that left him trapped in the dimension of the mysterious Prophets; now he's returned to his home universe—with powerful, godlike abilities. But his omnipotence is failing when he needs it most. Someone is killing the gods, and Sisko and the motley crew of the U.S.S. Theseus will have to travel to the deepest parts of space to stop them. Star Trek: Year Five lead writers Jackson Lanzing & Collin Kelly (Batman Beyond, Captain America) and artists Ramon Rosanas, Oleg Chudakov, Joe Eisma, and Erik Tamayo present a new ship, a new mission, and a lot of old friends! Sisko is joined by Commanders Data and Worf, and Dr. Beverly Crusher, of Star Trek: The Next Generation; Lt. Tom Paris, of Star Trek: Voyager; Ensign Lilly Sato, of Star Trek: Enterprise; Captain Montgomery Scott, of Star Trek: The Original Series, and Ben's son, Jake. But there are new faces as well, to surprise established fans while showing new readers the ropes. Collects the prequel short story ""A Perfect System"" from Star Trek #400 and issues #1–6 of the ongoing series.